Tuesday

January 27, 2015

January 27, 2015

Posted by **nishika** on Saturday, September 14, 2013 at 11:45pm.

- maths -
**Graham**, Sunday, September 15, 2013 at 12:25amUse: √(a+2√(ab)+b) = √a + √b

Too: √(a-2√(ab)+b) = √a - √b

√(5+2√6) + √(8-2√15)

= √(2+2√2√3+3) + √(8-2√15)

= √((√2+√3)^2) + √(8-2√15)

= √2 + √3 + √(8-2√15)

= √2 + √3 + √(5-2√3√5+3)

= √2 + √3 + √((√5-√3)^2)

= √2 + √3 + √5 - √3

= √2 + √5

**Answer this Question**

**Related Questions**

Math - 1)Find the standard deviation of the data set to the nearest tenth. (21,...

Calculus - Evaluate the indefinite integral: 8x-x^2. I got this but I the ...

Algebra - 1)A bookshelf holds 4 mysteries, 3 biograpghies, 1 book of poetry, and...

Math Help please!! - Could someone show me how to solve these problems step by ...

Mathematics - sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So...

Math(Roots) - sqrt(24) *I don't really get this stuff.Can somebody please help ...

Math - How do you find a square root of a number that's not a perfect square? I'...

Inequality - When I solve the inquality 2x^2 - 6 < 0, I get x < + or - ...

math,algebra,help - Directions are simplify by combining like terms. x radiacal ...

math calculus please help! - l = lim as x approaches 0 of x/(the square root of...